Solvent‐Adaptive Behavior of Oligospirobifluorenes at the Surface of Quartz Crystal Microbalances— A Conformational Process. Issue 8 (2nd March 2017) - Pyka, Isabella; Lubczyk, Daniel; Saiju, Mandira D. S.; Salbeck, Josef; Waldvogel, Siegfried R.
Abstract: Invited for this month's cover are the groups of Siegfried R. Waldvogel at the Johannes Gutenberg University Mainz and of Josef Salbeck at the University Kassel (both Germany). The image shows the swelling of a blowfish to represent the reversible conformational change of an oligospirobifluorene derivative upon solvation. Read the full text of the article at10.1002/cplu.201600583 . Abstract : "The oligospirobifluorenes studied do not change in size by simply swelling but rather by a more active change in conformation. This reminded us of a blowfish inflating itself upon changes in the environment." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201600583 ).